**Research Summary: Imam al-Bukhari's Methodology in Chronological Documentation of Prophetic Biography Events (Comprehensive Journal of Science, 2026)
aims to study the precise scientific methodology employed by Imam al-Bukhari in documenting the chronological sequence of Prophetic biography events in his Sahih, stemming from the scholarly significance of his work as the most authentic compilation after the Noble Quran. The importance of this study lies in the scarcity of specialized research on the chronological aspect in al-Bukhari's work and the need to highlight his meticulous approach in historical documentation.The research is organized around three main axes: The first focuses on the historical foundation of chronological documentation through the evolution of biographical recording. The second analyzes al-Bukhari’s methodology in selecting narrators and its relationship to chronological accuracy. The third reveals the purposive dimension in his documentation by linking narrations to their historical context.The study has yielded significant results, most notably: The distinction of al-Bukhari’s methodology in chronological precision through techniques of collective chain of transmission and thematic organization, its clear purposive character, and the contribution of precise narrator selection in enhancing the credibility of historical narrations.In conclusion, the research recommends developing modern analytical tools for studying chains of transmission, expanding the research scope to include other hadith sources, and utilizing the purposive methodology in studying the Prophetic biography, aiming to develop this important scholarly field.